Pathways to care for those at clinical high risk of developing psychosis. Issue 1 (28th June 2012) - Stowkowy, Jacqueline; Colijn, Mark A.; Addington, Jean
Abstract: Aim: Understanding the pathways to care is a prerequisite for early detection in first‐episode patients with psychosis. Less in known about the pathways to care for individuals at clinical high risk for psychosis. Methods: A sample of 35 clinical high risks for psychosis individuals were administered a semistructured questionnaire inquiring about pathways to care. Results: The majority of contacts were made to general practitioners (32.8%). Various symptoms of concern were reported among the sample, the most common being depression (15.9%) followed by anxiety (11.0%). Delusions/paranoia were the most frequent symptoms associated with successful referral to contacts (14.3%). Conclusion: Education on the pathway to successful access to care and treatment in a putatively prodromal for psychosis group of individuals is valuable information that can potentially aid in a faster discovery of these individuals and their access to treatment and care.